Islamisation de « l’intérieur du Maghreb » : les fuqahâ’ et les communautés rurales - Elise Voguet (Revue des Mondes Musulmans et de la Méditerranée)
The study of some maghribi’s fatwas from the XIVth and XVth centuries compiled in al-Māzūnī and al-Wanšarīsī collections reveals how the jurists prioritize the various rural groups they referred to : in an ideal Muslim community that they built, villagers, people of douars and ‘arab do not have the same status. But this “construction” does not provide evidence of the reality of the islamization of the region. Fatwas, however, offer the possibility to see the autonomy of rural groups regarding their religious life, the education of their children and the regulation of their conflicts.